2007
DOI: 10.1016/j.euroneuro.2006.04.011
|View full text |Cite
|
Sign up to set email alerts
|

CSF monoamine metabolites and lethality of suicide attempts in depressed patients with alcohol dependence

Abstract: Background: Alcohol dependence (alcoholism) and major depressive disorder are frequently comorbid and are risk factors for suicidal behavior. Monoaminergic abnormalities have been implicated in the pathophysiology of depression, alcohol dependence, and suicidal behavior. Lower cerebrospinal fluid (CSF) 5-hydroxyindolacetic acid (5-HIAA) levels are associated with higher lethality of suicide attempts in major depression and predict a higher rate of future suicide. We sought to study the relationship of CSF mono… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 31 publications
(32 reference statements)
0
14
1
Order By: Relevance
“…Nevertheless, alterations in the mechanisms that regulate HPA axis activity have been also hypothesized to predate the development of addiction, being part of inherited traits (Sher et al . 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, alterations in the mechanisms that regulate HPA axis activity have been also hypothesized to predate the development of addiction, being part of inherited traits (Sher et al . 2007).…”
Section: Discussionmentioning
confidence: 99%
“…As scores greater than 3 indicate the need for hospitalization to address injuries sustained during an attempt, some studies have considered attempts scored three or higher on the Lethality Scale to be of high-lethality (Malone, Corbitt, Li et al 1996;Oquendo, Placidi, Malone et al, 2003). Meanwhile, other studies (e.g., Sher, Oquendo, Grunebaum et al, 2007) have used a more stringent criterion to classify suicidal behavior as high-lethality, considering scores of 4 or higher to be high-lethality. Finally, among individuals who had accurate preconceptions about the lethality of their chosen method, the scale has been found to have good concurrent validity with the Suicide Intent Scale (Beck, Schuyler, & Herman, 1974;Beck, Beck, & Kovacs, 1975).…”
Section: Aggressionmentioning
confidence: 98%
“…This finding was supported by several subsequent studies (Jones et al, ; Lester, ) and was also shown to have some predictive value for future suicide in individuals with mood disorders (Mann et al, ; Nordstrom et al, ). Significant associations between low CSF 5‐HIAA levels and high lethality of the suicidal act were additionally reported (Mann et al, ; Placidi et al, ; Sher et al, ; Traskman‐Bendz et al, ). These lines of evidence suggest the potential independent significance of low CSF 5‐HIAA levels in the commitment and lethality of the suicidal act regardless of underlying depressive pathology.…”
Section: Resultsmentioning
confidence: 96%
“…However, the growth hormone peak responses to apomorphine did not significantly differ according to the lethality of the suicidal act . Serotonergic System 5-HIAA ↓5-HIAA CSF Jones et al, 1990Mann et al, 1996Sher et al, 2007, Placidi et al, 2001Traskman-Bendz et al, 1992Mann et al, 1996 ↓5-HT Plasma Tyano et al, 2006Platelet Mann et al, 1992Muck-Seler et al, 1996 Prolactin ↓Prolactin response to fenfluramine/flesinoxan Serum Correa et al, 2000Pitchot et al, 2005Duval et al, 2001Malone et al, 1996 SERT ↓PET SERT binding Midbrain, in vivo brain Miller et al, 2013 ↓B max ↑K m Platelet Marazziti et al, 2001c Roy, 1999 5-HT2A receptor ↑B max ↓K d Platelet Alda & Hrdina, 2000Pandey et al, 1990Hrdina et al, 1997Roggenbach et al, 2007c Mann et al, 1992Mcbride et al, 1994 depressed individuals who died by suicide (Merali et al, 2004;Poulter et al, 2010). Involvement of epigenetic processes has also been implicated in suicide, supported by studies that found GABA A receptor promoter hypermethylation in depressed suicide victims (Poulter et al, 2008).…”
Section: Other Molecular Mechanisms Of Suicidementioning
confidence: 99%